Reading the world – teaching visual analysis in higher education. Issue 1 (3rd April 2019) - Abas, Suriati
Abstract: This article provides a practical guide for teaching visual analysis to university students. By adapting Serafini's curricular and pedagogical framework for teaching multimodal representations to incorporate self-reflection, I evince how visual analysis can be taught in a writing course and similar introductory courses. Using a photograph that juxtaposed Edvard Munch's iconic image of The Scream, I aim to develop students' visual literacy (VL) skills in terms of generating interpretations and translating the visual-to-verbal for meaning-making. Given the increasing dominance of visual representations, VL is fundamental to meet contemporary needs and thus, should not be marginalized in higher education.